Modern Commercial Policy: Managed Trade or Retaliation? - Thomas J. Prusa; Susan Skeath (Wellesley College, Department of Economics, 2002)
In this paper we study worldwide antidumping (AD) case filing patterns in order to determine the extent to which economic versus strategic incentives explain the behavior of countries employing AD actions. We compare four main hypotheses. Two are motivated by the Bagwell- Staiger (1990) model of special protection and are consistent with the view that AD actions are used to prevent unfair trade: the 'big supplier' and the 'big change in imports' hypotheses. The other two hypotheses, tit-for-tat and the club effect, are outside the basic Bagwell-Staiger model and are consistent with the belief that strategic considerations influence AD actions. We find strong support that AD actions are directed at big suppliers, but far weaker evidence that AD actions are filed against suppliers whose imports have 'surged.' This finding casts doubt on the view that AD actions are primarily used to stop unfair trade practices because one would expect that such practices would be associated with large import gains. We also find very strong evidence that AD actions are used strategically to deter further use of AD and/or to punish trading partners who have used AD. Our findings reject the notion that the rise in AD activity is solely explained by an increase in unfair trading.
Keywords: 330; Antidumping; Retorsionsmaßnahme; Welt